Autologous orbicularis muscle for filling facial foldsan experimental and clinical study - Schellini, Silvana Artioli [UNESP]; Hirai, Flavio Eduardo [UNESP]; Hoyama, Erika [UNESP]; Mattos, Maila Karina [UNESP]; Chaves, Fernando Rodrigo [UNESP]; Pellizzon, Claudia Helena [UNESP]; Padovani, Carlos Roberto [UNESP] (Taylor & Francis, 2009)
Purpose: To present a technique for filling facial folds by using autologous orbicularis oculi muscle, based on an experimental model. Methods: two studies are presented: (1) an experimental study using 15 albino guinea-pigs from which a strip of the sural triceps muscle was removed and implanted in the subcutaneous tissue of the dorsal area. The animals were sacrificed 7, 30 and 60 days after the implantation, and the material was histologically evaluated. And (2%) an interventional prospective clinical trial carried out on 20 patients referred to blepharoplasty surgery. They received autologous preseptal orbicularis muscle for filling facial folds. The results where evaluated by patients satisfaction and clinical exam. Results: the sural tricep muscle, when implanted in the subcutaneous tissue, resulted in fibrosis. The patients whom received autologous orbicularis muscle implanted for filling facial folds showed that the procedure can be successfully carried out. Conclusions: autologous preseptal orbicularis muscle is a good material for filling facial folds. Cicatricial tissue will be formed on its implantation site, filling the tissue gap that forms the folds on the skin.
Keywords: Autologous implant; Blepharoplasty; Facial folds; Filling; Orbicularis oculi muscle; adult; animal experiment; animal tissue; clinical trial; controlled study; experimental model; experimental study; extraocular muscle; eyelid reconstruction; female; fibrosis; guinea pig; histopathology; human; human experiment; male; muscle graft; nonhuman; normal human; orbicular muscle; patient satisfaction; prospective study; skin; skinfold; subcutaneous tissue; surgical technique; tissue reaction; triceps brachii muscle; Adult; Animals; Disease Models, Animal; Esthetics; Eyelids; Facial Muscles; Female; Follow-Up Studies; Guinea Pigs; Humans; Immunohistochemistry; Intervention Studies; Male; Middle Aged; Oculomotor Muscles; Prospective Studies; Rejuvenation; Rhytidoplasty; Time Factors; Transplantation, Autologous; Treatment Outcome